2019
DOI: 10.4193/rhin19.005
|View full text |Cite
|
Sign up to set email alerts
|

Effect of gender on odor identification at different life stages: a meta-analysis

Abstract: Background: Although conflicting findings abound, gender-related differences in olfactory identification have received continuous attention. To our best knowledge, no systematic and quantitative research has examined gender differences in olfaction identification at various stages of life. The present study aimed to find out if there is gender difference in human olfaction identification in different life stages. Methodology: Studies cited in the PubMed database were searched from its inception to August 2017 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
32
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(36 citation statements)
references
References 82 publications
(141 reference statements)
3
32
0
Order By: Relevance
“…We found that olfactory performances were not influenced by sex. This is congruent with the results of a recent study and a meta-analysis that found no gender-related differences when performing olfactory tests in people aged > 50 years (21,22) .…”
Section: Discussionsupporting
confidence: 92%
“…We found that olfactory performances were not influenced by sex. This is congruent with the results of a recent study and a meta-analysis that found no gender-related differences when performing olfactory tests in people aged > 50 years (21,22) .…”
Section: Discussionsupporting
confidence: 92%
“…The explanation of this demographic trend is still not well understood. In the normal population, the olfactory dysfunction (OD) and gustatory dysfunction (GD) are commonly described more frequently with older age [ 17 , 18 ], while females outperformed males for taste [ 18 ] and smell [ 19 ]. In post-viral OD, a higher prevalence in middle-aged women (age 40–69 years) has been described [ 20 ].…”
Section: Discussionmentioning
confidence: 99%
“…report on 237 US patients with COVID-19 and anosmia, collated through an AAO-HNS resource, and state that loss of sense of smell was present before diagnosis in 73% of respondents, and was the initial symptom in 26.6% (4) , supporting the suggestion it is a useful early marker to prompt testing or self-isolation. Interestingly, these early reports have suggested a predominance of olfactory dysfunction in younger, female patients; this is in contrast to the general population, where olfactory function has been found to be lower in males an older patients (5,6) .…”
mentioning
confidence: 90%